Authorship, Patents, Citations, Acknowledgments, Tweets, Reader Counts and the Multifaceted Reward System of Science. Issue 1 (24th February 2016) - Desrochers, Nadine; Bowman, Timothy D.; Haustein, Stefanie; Mongeon, Philippe; Quan‐Haase, Anabel; Paul‐Hus, Adèle; Costas, Rodrigo; Larivière, Vincent; Pecoskie, Jen; Tsou, Andrew
ABSTRACT: Building upon well‐established paradigms brought forth by such theorists as Robert K. Merton, Pierre Bourdieu, and Blaise Cronin, the panel will span the full cycle of academic production to show, through various bibliometric measures and other quantitative and qualitative analyses, how the reward system of science is evolving. While there is strong evidence to suggest that such forms of dissemination as social media output and blogging are being incorporated into scientific practices, scientific impact still remains principally assessed using measures such as authorship and citations, whilst other elements, such as acknowledgements, have received varying levels of regard at various times. Disciplinary considerations also arise. Using a wide range of approaches, measures, and datasets, the panelists will establish links between their individual research to create an empirically driven picture of the reward system of science and its indicators. Through the use of the Polldaddy application, audience members will answer questions and create an overview of their perception of the reward system of science.